Pelatihan Membuat Konten Instagram pada Karang Taruna Sedatigede - Fibriana, Adinda Herna; Rochmaniah, Ainur; Febriana, Poppy (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2024)
Karang Taruna Sedatigede is one of the most advanced youth organizations in Sidoarjo, judging by their programs. Karang Taruna Sedatigede uses Instagram as one of the media in promoting their activities. However, when viewed from a distance their account posts look less productive and the content is only in the form of pictures. So that it is necessary to increase the productivity of Instagram content for promotion to support the dissemination of information regarding work programs at Karang Taruna Sedatigede. From this, the community service activity "Training on Making Instagram Content at Karang Taruna Sedatigede" was carried out starting with poster content training on the Canva application. Furthermore, video editing training is carried out so that their Instagram content is not monotonous with only pictures, but also video content. After these two sessions, assistance was carried out for the execution of the content resulting from the training that had been carried out. From all of these activities, the results obtained were that Karang Taruna members became motivated and their productivity in creating content increased. This is proven by the promotional video content that they uploaded after the training and mentoring period was over, which had never been done before by Karang Taruna Sedatigede.